2017
DOI: 10.1111/aogs.13147
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolism and in vitro fertilization - a systematic review

Abstract: The antepartum risk of VTE after IVF is doubled, compared with the background pregnant population, and is in turn related to a very high risk of VTE after OHSS in the first trimester. We recommend that IVF patients with OHSS be prescribed low-molecular-weight heparin during the first trimester, whereas other IVF patients should be given thromboprophylaxis based on the same risk factors as other pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 44 publications
(111 reference statements)
1
58
0
6
Order By: Relevance
“…Little data is available regarding risk of thromboembolism during oocyte or embryo cryopreservation alone (i.e. without fresh embryo transfer), but concern for this complication is supported by the observation that risk of venous thromboembolism is significantly higher in the first trimester of pregnancy following in vitro fertilization and fresh embryo transfer (and 100-fold when treatment was complicated by OHSS), as compared to spontaneous pregnancies [ 22 ]. Aspirin was also considered for this patient, which may reduce the risk of OHSS as well as thromboembolism [ 9 ], but the decision was made to proceed without aspirin due to concern for hemostasis during oocyte retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Little data is available regarding risk of thromboembolism during oocyte or embryo cryopreservation alone (i.e. without fresh embryo transfer), but concern for this complication is supported by the observation that risk of venous thromboembolism is significantly higher in the first trimester of pregnancy following in vitro fertilization and fresh embryo transfer (and 100-fold when treatment was complicated by OHSS), as compared to spontaneous pregnancies [ 22 ]. Aspirin was also considered for this patient, which may reduce the risk of OHSS as well as thromboembolism [ 9 ], but the decision was made to proceed without aspirin due to concern for hemostasis during oocyte retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 16 17 ] A recent systematic review has confirmed that the antepartum risk of VTE after IVF is doubled (odds ratio, 2.18; 95% confidence interval, 1.63–2.92) in comparison with the background normal pregnant population. [ 18 ] The incidence of VTE has been reported as 0.1%–0.5% of all IVF cycles started and the risk of arterial thrombosis is much lower. Nearly 70% of reported cases are venous thrombosis and 30% are arterial.…”
Section: Discussionmentioning
confidence: 99%
“…However, a very recent analysis by Sennström et al . [ 11 ] reported that IVF results in twofold increase in the risk of thromboembolic events when compared to non-IVF pregnancies. Moreover, hospitalized IVF patients due to ovarian hyperstimulation syndrome had 100-fold increased risk of thromboembolic events when compared to non-IVF pregnant population.…”
Section: Discussionmentioning
confidence: 99%